Sustainable resource management policy of national economic development - Koval, V.; Savina, N.; Sribna, Ye.; Osipova, A.; Kapelista, I.; Petrovska, S. A.; Петровська, С. А. (IOP Conference Series: Earth and Environmental Science: Vol. 1269: 3rd International Conference on Environmental Sustainability in Natural Resources Management (Batumi, Georgia, 20.10.2023), 2023)
У статті розглянуто механізм можливого повного забезпечення стратегічними ресурсами з метою реалізації концепції сталого розвитку. Вказано два основних підходи до накопичення ресурсів: 1) перший підхід, спрямований на збереження стратегічного запасу енергоресурсів, що передбачає концентрацію ресурсів для забезпечення стабільності та безпеки енергопостачання; 2) другий підхід полягає в акумулюванні фінансових активів шляхом отримання доходу та дозволяє формувати фінансовий резерв. У випадку першого підходу країна, як і Сполучені Штати, стратегічно накопичила запаси сирої нафти, прикладом чого є створення Стратегічного резерву нафти (SPR) у 1970-х роках. Відсоткове співвідношення експорту сирої нафти США щодо їх щоденного споживання нафти в Сполучених Штатах з 1980 по 2023 рік було розраховано та детально описано в дослідженні з такими тенденціями, як падіння на 1% у 2005 році та подальше збільшення на 156% у 2023 році. Виявлено та визначено вплив технологічних і геополітичних факторів на ці зміни.

The article considers the mechanism of possible full supply of strategic resources for the purpose of implementing the concept of sustainable development. Two main approaches to the accumulation of resources are indicated: i) the first approach, aimed at maintaining a strategic stock of energy resources, which involves the concentration of resources to ensure the stability and security of energy supplies; ii) the second approach consists in the accumulation of financial assets through the receipt of income and allows the formation of a financial reserve. In the case of the first approach, the country like the United States strategically accumulated crude oil reserves, exemplified by the establishment of the Strategic Petroleum Reserve (SPR) in the 1970s. The percentage ratio of US crude oil exports relative to their daily oil consumption in the United States from 1980 to 2023 was calculated and detailed in the research, with trends such as a decline of 1% in 2005 and a subsequent increase of 156% in 2023 being revealed, and the impact of technological and geopolitical factors on these changes was determined.

В статье рассмотрен механизм возможного полного обеспечения стратегическими ресурсами для реализации концепции устойчивого развития. Указаны два основных подхода к накоплению ресурсов: первый подход, направленный на сохранение стратегического запаса энергоресурсов, предусматривающий концентрацию ресурсов для обеспечения стабильности и безопасности энергоснабжения; 2) второй подход состоит в аккумулировании финансовых активов путем получения дохода и позволяет формировать финансовый резерв. В случае первого подхода страна, как и Соединенные Штаты, стратегически накопила запасы сырой нефти, примером которых является создание Стратегического резерва нефти (SPR) в 1970-х годах. Процентное соотношение экспорта сырой нефти США по поводу ежедневного потребления нефти в Соединенных Штатах с 1980 по 2023 год было рассчитано и подробно описано в исследовании с такими тенденциями, как падение на 1% в 2005 году и дальнейшее увеличение на 156% в 2023 году. Выявлено и определено влияние технологических и геополитических факторов на эти изменения.
Keywords: Україна; економіка; забезпечення стратегічними ресурсами; стратегічні ресурси; Ukraine; economy; provision of strategic resources; strategic resources; экономика; Украина; обеспечение стратегическими ресурсами; стратегические ресурсы